2018
DOI: 10.1016/j.jadohealth.2017.11.301
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Smoking and Electronic Cigarette Use in a Cohort of Young People

Abstract: PurposeElectronic cigarette (e-cigarette) use is associated with smoking initiation among young people; however, it is also possible that smoking is associated with e-cigarette initiation. This study explores these associations among young people in Great Britain.MethodsA longitudinal survey of 1,152 11- to 18-year-olds was conducted with baseline in April 2016 and follow-up between August and October 2016. Logistic regression models and causal mediation analyses assessed whether (1) ever e-cigarette use and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(127 citation statements)
references
References 37 publications
(91 reference statements)
6
115
4
2
Order By: Relevance
“…Using parameters from the CASP tool for cohort studies, the included studies were generally of good quality ( Table 1) while risk of bias was mainly low ( Table 2). Over all of the eight included studies 20,[42][43][44][45][46][47][48] there were a total of 73076 adolescents aged 10-19 years ( Table 3). Five of the studies used a crosssectional survey design 20,45-48 while three [42][43][44] were longitudinal (prospective) designs and were able to be included in a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using parameters from the CASP tool for cohort studies, the included studies were generally of good quality ( Table 1) while risk of bias was mainly low ( Table 2). Over all of the eight included studies 20,[42][43][44][45][46][47][48] there were a total of 73076 adolescents aged 10-19 years ( Table 3). Five of the studies used a crosssectional survey design 20,45-48 while three [42][43][44] were longitudinal (prospective) designs and were able to be included in a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Smoking initiation does not mean regular use, however it can be taken as a potential starting point that could easily progress to regular use of a substance 49 . Three longitudinal studies [42][43][44] Almost half of those who had tried smoking had tried an e-cigarette. 42.8% of young people who had used e-cigarettes reported that they had never smoked tobacco.…”
Section: Smoking Initiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that ENDS are being used in cessation attempts (Kalkhoran and Glantz 2016;Mantey et al 2017;Weaver et al 2018) as well as by people who choose to continue their nicotine habit either for potential / perceived health benefits (Spears et al 2018;Stokes et al 2018) or social acceptability (Berg et al 2014;Romijnders et al 2018) compared with tobacco smoking. Widespread availability of such devices, particularly with adolescent age ranges, sparks concern that ENDS may facilitate the development of nicotine dependence without any prior use of combustible tobacco products (Fulton et al 2018;Martinasek et al 2018) and may even increase the odds of later initiation of combustible tobacco use (East et al 2018;Loukas et al 2018;Primack et al 2018), a relationship that may be mediated by the nicotine content in the e-cigarettes (Goldenson et al 2017).…”
Section: Introductionmentioning
confidence: 99%